Representações sociais de sustentabilidade no ensino de ciências - Lindenmaier, Diogo de Souza (2019)
The phenomenon of sustainability and sustainable development has shown significant adherence to the most diverse fields and human activities. It is directly related to socio-environmental demands, as well as geopolitical issues, and in its development has focused on education as an expansion strategy. The aim of this study is to know the social representations of sustainability that circulate in science teaching in Brazil, and to understand their implications for Brazilian education. We also work with the thesis that there is a polysemy as to the concept of, and that by mobilizing a series of representations eventually elevate the phenomenon to a mythological dimension. As theoretical support was used the Theory of Social Representations originally proposed by Moscovici (1981). The empirical material that provided the source for the research information was the biology textbook collections available for PNLDEM 2018, totaling eight volumes; The main documents that guide Brazilian education were also investigated, among them the National Education Plan, the National Curriculum Guidelines, the National Curriculum Parameters, the new Common National Curriculum Base and the Enem Reference Matrix; The third item investigated were publications in periodicals A1, A2 and B1 of the Teaching Area from 1996 to 2018. The methodology adopted to Analyze Textual Discourse (ATD), where from the emerging categories were carried out new understandings that led the social representations of sustainability. The overall results account for social representations that refer to nature as natural resources; nature management; risk, catastrophe and salvationism; science, technique and technology; knowledge, interdisciplinarity and complexity; sustainability as a qualifying principle; naive representation of sustainability; the United Nations, international conferences and governance; sustainable societies and eco-development; individual accountability; and the critique of sustainability. The emergence of various social representations points to sustainability as a dubious and multifaceted phenomenon, and confirms its modern mythological dimension, centered on the maintenance of development and the continuity of the modernity project.